Cultures of contamination legacies of pollution in Russia and the U.S. (Amsterdam ; Oxford : Elsevier JAI, 2007)
This volume ponders the cultures that generated the bulk of our global contamination legacy. Insight is sought into its creation and an understanding of differences in how it is being addressed. Hopefully the illumination of the problem will contribute to a better understanding of the constraining conditions and will help guide us in meeting the twin challenges created by the legacy of contamination: how to stop it and how to address what we already have done. Section one focuses on the psycho-social dynamics of chemical contamination. Section two deals with nuclear events, both accidents, but also the closed cities and closed society needed to produce a nuclear context. Section 3 addresses mitigations, dominated by 4 out of 5 chapters addressing Russia. And section four provides perspectives, comparative pieces addressing secrecy in nuclear programs, distorted risk communication in the aftermath of the World Trade Center Disaster, environmental altruism and in core social response to environmental challenges. It examines the cultures most responsible for global contamination. It adopts a global and practical perspective, with case examples from the United States and Russia. It seeks to stop contaminations from taking place in the future and positively address those from the past. This book series is available electronically at website.
Sustainability and the need to deal with the contaminated legacy: a comparison of Russia and the U.S. / Michael R. Edelstein -- pt. 1. The dynamics of a contaminated community. Section 1. Introduction. The Love Canal: social science research in a community in crisis / Adeline G. Levine -- Forging change in a contaminated Russian city: a longitudinal view of Kirishi / Olga Tsepilova -- Sokol: seeing the forests for the trees / Antonina Kulyasova and Ivan Kulyosov -- The case of the Pinewood landfill: the politics of risk, rationality, and the disposal of hazardous waste / Nicholas D. Martyniak ... [et al.] -- Fear of cancer in a rural Appalachian community following notification of an environmental hazard / Janice L. Hastrup ... [et al.] -- Toxic water and the anthill effect: the development of a subculture of distress in a once contaminated community / Stephen R. Couch and Anne E. Mercuri -- pt. 2. Closed cities, secret accidents and social adaptations -- Section 2. Introduction. Closed city, open disaster / Nadezhda Kutepova and Olga Tsepilova -- The most contaminated place on earth: community response to long--term radiological disaster in Russia's southern urals / Natalia Mironova, Maria Tysiachniouk and Jonathan Reisman -- Psycho--social consequences due to radioactive contamination in the Techa River region of Russia / Michael R. Edelstein and Maria Tysiachniouk -- Environmental risk perception after Chernobyl / Irina A. Zykova -- Habitual risk taking in Dzerzhinsk: daily life in the capital of Soviet chemistry / Alla Bolotova -- Hanford: the closed city and its downwind victims / Michael R. Edelstein -- pt. 3. Mitigations. Section 3. Introduction. A grassroots perspective on the Brownfields and Superfund programs / Madelyn Hoffman -- Cleaning up from the Cold War: medical, ecological and psychological aspects of the Russian experience with chemical weapons destruction / Boris N. Filatov ... [et al.] -- Chernobyl: a liquidator's stody / Lyudmila V. Smirnova and Michael R. Edelstein -- Into thin air: training children to live in polluted environment / Oleg S. Glazachev -- Social remediation: contamination as an impetus for ecological learning / Lyudmila V. Smirnova -- pt.4. Perspectives. Section 4. Introduction. Coming clean after 9/11: the continuing World Trade Center disaster / Michael R. Edelstein and Catherine McVay Hughes -- Environmental altruism: a comparison of Russia and the United States / Margaret Gibbs ... [et al.] -- The parable of the Lions Bridge: potentials for mutual learning between cultures of contamination / Michael R. Edelstein and Lyudmila V. Smirnova.
Registro generado automáticamente a partir de metadatos facilitados por Emerald Publishing
Description based on print version record.